(untitled) (International Journal of Environmental Sciences, 2025)
Ambush marketing is a complex challenge faced during the intersection of Intellectual property rights and sports brand marketing. Most of the time it is not illegal, but it frequently compromises the exclusivity given to the official sponsors, resulting in conflicts with official sponsors for the unauthorised commercial association, especially in prominent events like Olympic Games. This paper critically examines the case of United States Olympic & Paralympic Committee (USOPC) v. Puma, where Puma is not an official Olympic sponsor but attempted to register a trademark as “PUMA TOKYO 2021”. The United States Patent and Trademark Office (USPTO) rejected the registration as it will create the potential false association and dilution of Olympic goodwill. Even before the court ruled the registration. This paper also seeks to explore the ramifications of this administrative decision for trademark law, the regulatory measures on non official sponsors and the extent scope of Olympic property rights. Additionally this paper will compare this rejection of registration with international precedent to suggest a unified legal framework for tackling ambush marketing around the world.